Identification and expression analyses of new genes associated with ciprofloxacin resistance in Vibrio parahaemolyticus. (November 2019) - Zhou, Haibo; Liang, Ying; Gao, Lu; Ren, Jianluan; Xue, Feng; Guo, Dehua; Jiang, Yuan; Yang, Zhenquan; Lian, Lele; Dai, Jianjun
Abstract: Quinolone-resistant foodborne pathogens have become an important public health concern, however, little is known about the molecular mechanism of ciprofloxacin (CIP) resistance among Vibrio parahaemolyticus isolates. This study aimed to explore new genes implicated in resistance to CIP in genome-wide. CIP susceptibility of six V. parahaemolyticus isolates was analyzed by disk diffusion and micro-broth dilution methods. To establish a model for CIP-resistant V. parahaemolyticus, in vitro continuous subcultures in drug gradient medium were adopted, and minimum inhibitory concentrations (MICs) was eventually increased by 64–128 times. Quinolone resistance determining region (QRDR) genes were screened by polymerase chain reaction (PCR), and it was demonstrated that there were mutations of gyrA at position 83 and parC at position 85. In addition, whole genome sequencing (WGS) analysis showed that an emergence of joint variations was found in ten genes, and the expression of those was detected by reverse transcription quantitative PCR (RT-qPCR). Collectively, these results suggest that the mutation of these novel gene sequences and the increase of expression of those genes may be related to CIP resistance in V. parahaemolyticus, which provide insights into the molecular basis for the phenotypic variations in bacterial antibiotic resistance, and thus may help clinicians develop more efficient strategies for antibiotic therapies. Graphical abstract: Unlabelled Image Highlights: Whole genome resequencing revealed genetic diversity from V.parahaemolyticus strains. New mutations associated with ciprofloxacin resistance are diverse among isolates despite of the same environmental exposure. Increased expression of ciprofloxacin resistance related genes in the mutants.